CPR quality with rotation of every 1 versus 2 minutes as characteristics of rescuers: A randomized crossover simulation study. Issue 10 (10th March 2023) - Kim, Dong Hun; Seo, Young Woo; Jang, Tae Chang
Abstract : Background: Fatigue and rotation time are key factors affecting the quality of cardiopulmonary resuscitation (CPR). This study aimed to investigate the effects of rotation time on CPR duration, and sex on chest compression quality. Methods: In this randomized crossover simulation study, we enrolled 100 paramedic students stratified by sex and randomly grouped into 28 male and 22 female pairs. In the 2- and 1-minute scenarios, 2 participants performed CPR for 20 minutes with a rotation cycle of 2 minutes and 1 minute, respectively. After taking a break, they changed over and performed CPR again for 20 minutes. The switching of roles was performed with the students positioned on opposite sides of the mannequin. For chest compression quality, a set was defined as CPR performed by 1 pair in a 2-minute scenario for 4 minutes. The quality of CPR in each set was compared between the 2 groups. Results: The 1-minute group showed significantly higher chest compression depth than the 2-minute group (54.0 [51.5–57.0] vs 52.5 [48.5–56.5] mm, P = .001, respectively). The female 2-minute group showed decreased chest compression depth over time, and the 1-minute group showed significantly increased chest compression depth during all sets except the 2nd set (54.0 [51.9–55.1] vs 50.5 [48.5–53.8] mm [ P = .030], 52.3 [49.4–54.5] vs 50.8 [47.0–53.1] mm [ P = .080], 52.8 [49.8–54.5] vs 48.8 [45.4–51.6] mm [ P = .002], 51.5 [48.5–53.3] vs 48.3 [44.5–50.6] mm [ P = .004], and 50.8 [48.9–54.1] vs 47.5 [44.6–50.1] mm [ P = .001], respectively). The fatigue scores in the 2-minute group were significantly higher during sets 4 and 5 than those in the 1-minute group. Conclusion: When rescuer fatigue increases during prolonged CPR owing to their physical strength and skill levels, the rotation of rescuers every minute would be helpful in maintaining high-quality CPR.